Novel therapeutic strategy for unilateral diaphragmatic paralysis in children with univentricular circulation: EMG-guided diaphragmatic stimulation - Kratz Tobias; Ruff Roman; Koch Timo; Breuer Johannes; Asfour Boulos; Herberg Ulrike; Bierbach Benjamin (Current Directions in Biomedical Engineering)
Unilateral diaphragmatic paralysis in children with univentricular circulation poses significant challenges, including impaired hemodynamics and increased postoperative complications. Restoring diaphragmatic function is crucial to mitigate these risks. This study investigates the feasibility of automated stimulation of the paretic diaphragm half using electromyography (EMG) signals from the non-paretic side following transection of the right phrenic nerve. Our findings demonstrate successful automated stimulation, suggesting the potential development of an EMG-triggered synchronized unilateral diaphragmatic pacemaker. This innovative approach holds promise as a novel therapeutic intervention for managing unilateral diaphragmatic paralysis in pediatric patients with univentricular circulation.